Mechanical bowel obstruction due to colonic hemangioma: Report of a case - Tolga DEMİRBAŞ,; Necdet GÜLER,; Cemil ÇALIŞKAN,; Barış GÜRCÜ,; Başak DOĞANAVŞARGİL,; Mustafa KORKUT, (Turkish Journal of Gastroenterology, 2019)
-